Review and Prospect of Chinese Study on Rosa Luxemburg. Issue 1 (2nd January 2016) - Jiahong, Ma
ABSTRACT: This article reviews the history of research on Rosa Luxemburg in China and concludes the characteristics of recent study. Although the study on Rosa Luxemburg has already made great progress, it still has many shortcomings and limitations. First, influenced by Western Marxism, the study contains a trend of over abstraction and modernization of the thought of Rosa Luxemburg; second, it may be far from reality to regard historical materialism as a totality method; additionally, the study is not sufficient in cognizing the limitation of Rosa Luxemburg's thought. After elaborating these problems, this article will try to point out the possible prospects of the study on Rosa Luxemburg in the future.